Evaluasi Efektivitas Pengendalian Risiko Atas Penjualan Property Di PT X - Putri, Aulia Yunianti; Kurniawan, Aceng (STIM-LPI Makassar, 2024)
The progress and development of the business environment today have evolved rapidly and precisely. The increasingly competitive industrial development over time necessitates every company to be ready to face intensifying competition. Essentially, risks are inherent in all aspects of human life and activities, from personal matters to corporate affairs, from lifestyle issues to disease patterns, from waking up to sleeping at night, and much more. Risk management experts, both domestically and internationally, have various definitions of what risk and risk management entail. However, generally, risk can be defined in various ways, such as an adverse event or a deviation of outcomes from expectations. This research employs a descriptive qualitative approach to evaluate the effectiveness of risk control in sales at PT